L’explication interthéorique en relations internationales : quelques jalons pour une synthèse du réalisme structurel américain et de la géopolitique française contemporaine. - Young, John (Études internationales, 1987)
Structural realism is currently at the center of international political theory in the United States. Sociological interpretations of ethnocultural or linguistic hegemony aside, this scientifically rigorous theorizing can stand on its intrinsic merits and is destined to exercise a major influence on future efforts to construct explanatory models of international political relations. This article sets out why that is so by drawing a profile of a viable deductive macrotheory of Interstate politics. The new realist theory is distinguished from its more overtly normative and prescriptivist antecedents which sought to come to terms with the contending claims of power and ethics in world politics and from the self-conscious scientism of earlier Systems thinking which emphasized unit-processed interaction patterns. Structural realism has broken free from the holistic organicism of Systems theory, tributary to biological models, to align the theory-building enterprise with the more successful formal structuralism of the physico-chemical sciences which places a premium on the generic description of logico-mathematical group structures arrived at through the inventive deduction or axiomatic decision of their constituent unit s. The exemplar text of American structural realism posits a form of what Piaget called 'relational' structuralism predicated on distributions of power resources among the international System's unit s. This focus on internal or necessary asymmetric relations between and among polarizing and dependent units renders structural realism a choice object for synthesis with inductively generated geopolitical constructs which stress microstructural configurations of relative capabilities. The current wave of geopolitical writing in the French language is drawn on to demonstrate how the procedures of intertheoretical reduction can be employed to enrich structural realism's explanation of system-level constraints on state action via the introduction of a spatiotemporal component.